Pengaruh Kemampuan Kerja, Kepuasan Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. BPR Syariah Artha Pamenang Kediri - Elfida Rizqia Eltatiana; Taufik Akbar; Erwin Syahputra (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The aim of this research is to explain the influence of work ability, job satisfaction and physical work environment on employee performance at PT. BPR Syariah Artha Pamenang Kediri. The research method used is a quantitative method using a questionnaire as research data. This research uses a saturated sampling technique. The population of this study was 32 people and the sample used was all employees, namely 32 respondents. The analysis technique used is multiple linear regression analysis, t test, f test and coefficient of determination (R2). The results of this test can be concluded that the t test results show that the work ability variable partially has a significant positive effect on employee performance with a significant value of 0.003 and a t-count value of 1.753. The job satisfaction variable partially has a significant positive effect on employee performance with a significant value of 0.000 and a t value of 2.347. The physical work environment variable partially has a significant positive effect on employee performance with a significant value of 0.002 and a t value of 1.771. And the results of the f test show that work ability, job satisfaction and the physical work environment have a significant effect on employee performance with a significant value of 0.000 and an F value of 19.889.